Comparative Study Of Al-Ghazali Thought and Ibn Rushd in the Perspective of Islamic Theology - Surni Kadir (Universitas Muhammadiyah Palu, 2024)
This article discusses the comparison of the thoughts of two great figures in the history of Islamic theology, namely Al-Ghazali and Ibn Rushd, and the impact of their contributions to the development of Islamic theology. Al-Ghazali is known as a scholar who has a significant role in combining Islamic philosophy and theology, while Ibn Rushd is known for his more rational and philosophical approach to religion. This article reviews the traces of the two thoughts, covering theological concepts, views on philosophy, and approaches to controversial issues in Islamic theology. Through this comparison, this article attempts to identify the similarities and differences in the views of the two, as well as analyze how their thinking contributed to the development of Islamic theology. The results of the analysis show that Al-Ghazali and Ibn Rushd, although they had different approaches, both made invaluable contributions to Islamic theological thought. Al-Ghazali with his emphasis on mystical experience and his rejection of some elements of philosophy, while Ibn Rushd with his more rational and critical approach to theology. The thought of both has shaped and influenced Islamic theological thought in the next period. The implications of Al-Ghazali and Ibn Rushd's thoughts on theological diversity in Islam are also noted, and how their thoughts have become an inspiration for various schools of thought in the Islamic world. By detailing and analyzing the differences and similarities in the thought of Al-Ghazali and Ibn Rushd, this article provides in-depth insight into the evolution of Islamic theology as well as the important contributions of these two thinkers in understanding and formulating the rich and complex theological foundations of Islam.